Pengaruh Ibu yang Bekerja dan Ibu yang Tidak Bekerja Terhadap Perkembangan Sosial Emosional Anak Usia Dini di RW 07 Kelurahan Tanjung Perak Kota Surabaya - Yulia Dwi Safitri; Gunarti Dwi Lestari (J+PLUS UNESA, 2023)
This study aims to determine the influence of working mothers and non-working mothers on social emotional development of early childhood in RW 07 Tanjung Perak Sub-District, Surabaya City. This study examines the influence of working mothers and non-working mothers on social emotional development of early childhood. This type of research is Ex Post Facto Causal Comparative Research. The data in the study were taken using a questionnaire which was distributed to research respondents with a population of 62. The data analysis technique used the T test. The results showed that: (1) working mothers and non-working mothers have an influence on the social emotional development of young children (2) Mothers who do not work have a greater influence on the social emotional development of early childhood than working mothers. For working mothers and non-working mothers, it is hoped that they will be able to maintain and improve the social emotionality of their children.